What drives the differences in domestic value added in exports between old and new E.U. member states?. Issue 1 (1st January 2018) - Vrh, Nataša
Abstract: Domestic value added in exports has lately become a key measure of a country's global competitiveness. This paper analyses the potential drivers of the differences in domestically generated value added in exported goods between 'new' (CEE-10) and 'old' (EU-15) countries. The analysis focuses on the role played by intangible investments, human capital and foreign direct investment. By studying export performance at the industry level for the period 2000–2011, this paper finds that differences in the share of domestically generated value added depend on investments in intangible capital, in particular investments in research and development. CEE-10 countries suffer from a distinct lack of investments in intangible capital, which is currently only sufficient to enable their mere participation in global value chains. Further, inward F.D.I. causes a reduction in demand for domestic inputs for both groups of countries and hence lowers D.V.A. in exports, while CEE-10 countries are also found to be upgrading global value chains by undertaking outward F.D.I.